2009
DOI: 10.2478/s11535-009-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced response in E. coli and S. cerevisiae: different stages of the flow of the genetic information

Abstract: Adaptation to oxidative stress is a major topic in basic and applied research. Cell response to stressful changes is realized through coordinated reorganization of gene expression. E. coli and S. cerevisiae are extremely amenable to genetic or molecular biological and biochemical approaches, which make these microorganisms suitable models to study stress response at a molecular level in prokaryotes and eukaryotes, respectively. The main focus of this review is (i) to discuss transcriptional control of global r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 89 publications
(178 reference statements)
0
30
1
1
Order By: Relevance
“…Earlier we suggested that cells treated with low sublethal concentrations of hydrogen peroxide accumulated non-active stress-protective molecules, further activation of which made microorganisms resistant to lethal concentrations of H 2 O 2 . 25,47 Overall, microorganism exposure to mild stress leads to the acquisition of cellular resistance to lethal stress. 5,6,[23][24][25] Here we found that H 2 O 2 pre-incubation increased the survival of yeast exposed to 200 mM AA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier we suggested that cells treated with low sublethal concentrations of hydrogen peroxide accumulated non-active stress-protective molecules, further activation of which made microorganisms resistant to lethal concentrations of H 2 O 2 . 25,47 Overall, microorganism exposure to mild stress leads to the acquisition of cellular resistance to lethal stress. 5,6,[23][24][25] Here we found that H 2 O 2 pre-incubation increased the survival of yeast exposed to 200 mM AA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, yeast exposed to a mild dose of oxidative stress could subsequently survive an otherwise lethal dose of the same or another stress. 5,6,[23][24][25] The latter is known as 'cross-adaptation' or 'cross-protection'. In the present work, we examined the influence of cell pre-adaptation by sublethal concentrations of hydrogen peroxide on yeast survival under acid stress.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic application of sublethal concentrations of H 2 O 2 in budding yeast induces the transcription of genes encoding both the cytosolic Cu/Zn-dependent and the mitochondrial Mn-dependent superoxide dismutases SOD1 and SOD2 (13,14) as well as an increase in levels of the corresponding proteins (13 also induces transcription of the superoxide dismutase sodA in Escherichia coli (15) and the transcription and activity of MnSOD, but not Cu/Zn-SOD in rat cells (16). To determine whether induction of Sod1p and/or Sod2p activity underlies the reduction in O 2 − levels that accompanies increases in intracellular H 2 O 2 , we measured the activities of Sod1p and Sod2p under CR and non-CR conditions in wild-type and CTA1 mutant cells.…”
Section: Elevated H 2 O 2 Levels Induced By Cr or Inactivation Of Catmentioning
confidence: 99%
“…Specific mechanisms may differ substantially, but a decrease in the activity is a common event. Increases in the activities of antioxidant and associated enzymes under oxidative stress are usually connected with their de novo synthesis [29,35] or activation of preexisting inactive molecules [5,6,52]. Although activation of inactive enzyme molecules is still debatable issue, up-regulation of their biosynthesis is well-established.…”
Section: Fig 2 Relationships Between the Dose Of An Inducer Of Oxidmentioning
confidence: 99%